In-situ quantitative TEM investigation on the dynamic evolution of individual twin boundary in magnesium under cyclic loading. (15th October 2019) - Liu, Bo-Yu; Prasad, K. Eswar; Yang, Nan; Liu, Fei; Shan, Zhi-Wei
Abstract: Quantification of dynamics of individual twin boundary (TB) migration such as the velocities and corresponding stresses, is of critical importance for understanding the deformation behavior of magnesium alloys. By conducting in-situ cyclic loading experiments on submicron magnesium pillars inside transmission electron microscope (TEM), the dynamics of individual TB migration and the associated twinning-detwinning phenomena are systematically investigated. It is found that the TB can migrate forward and backward under each cyclic loading paths, corresponding to the twinning-detwinning cycles. The TB morphology changes constantly during its migration. Surprisingly, the stress required for TB migration is found to be higher in compression than in tension, and the TB migration velocity in compression is slower than in tension. Such asymmetry is proposed to be associated with different defect environment on either side of TB and the TB structure per se. The considerable amount of energy absorbed during the TB migration is believed to account for at least part of the good damping properties of Mg. Our results are also expected to benefit the modeling of deformation twinning behavior in Mg and other HCP metals. Graphical abstract: Image 1